Respuesta :

msm555

Answer:

[tex]x^2 - x - 1 = 0[/tex]

Step-by-step explanation:

To rewrite the equation [tex]x^2 = 1 + x[/tex] in standard form, we need to set the equation equal to zero and combine like terms. The standard form of a quadratic equation is:

[tex]ax^2 + bx + c = 0[/tex]

Given the equation:

[tex]x^2 = 1 + x[/tex]

We'll move all the terms to one side to set the equation equal to zero:

[tex]x^2 - x - 1 = 0[/tex]

Now, the equation is in standard form:

[tex]x^2 - x - 1 = 0[/tex]

ACCESS MORE